Impact of COVID-19 on gastroenterology fellowship training: a multicenter analysis of endoscopy volumes - Paleti, Swathi; Sobani, Zain A.; McCarty, Thomas R.; Gutta, Aditya; Gremida, Anas; Shah, Raj; Nutalapati, Venkat; Bazerbachi, Fateh; Jesudoss, Randhir; Amin, Shreya; Okwara, Chinemerem; Kathi, Pradeep Reddy; Ahmed, Ali; Gessel, Luke; Hung, Kenneth; Masoud, Amir; Yu, Jessica; Mony, Shruti; Akshintala, Venkata; Jamil, Laith; Nasereddin, Thayer; Kochhar, Gursimran; Vyas, Neil; Saligram, Shreyas; Garg, Rajat; Sandhu, Dalbir; Benrajab, Karim; Konjeti, Rajesh; Agnihotri, Abhishek; Trivedi, Hirsh; Grunwald, Matthew; Mayer, Ira; Mohanty, Arpan; Rustagi, Tarun (Endoscopy International Open, 2021)
Background and study aims The COVID-19 pandemic has had a profound impact on gastroenterology training programs. We aimed to objectively evaluate procedural training volume and impact of COVID-19 on gastroenterology fellowship programs in the United States. Methods This was a retrospective, multicenter study. Procedure volume data on upper and lower endoscopies performed by gastroenterology fellows was abstracted directly from the electronic medical record. The study period was stratified into 2 time periods: Study Period 1, SP1 (03/15/2020 to 06/30/2020) and Study Period 2, SP2 (07/01/2020 to 12/15/2020). Procedure volumes during SP1 and SP2 were compared to Historic Period 1 (HP1) (03/15/2019 to 06/30/2019) and Historic Period 2 (HP2) (07/01/2019 to 12/15/2019) as historical reference. Results Data from 23 gastroenterology fellowship programs (total procedures = 127,958) with a median of 284 fellows (range 273–289; representing 17.8 % of all trainees in the United States) were collected. Compared to HP1, fellows performed 53.6 % less procedures in SP1 (total volume: 28,808 vs 13,378; mean 105.52 ± 71.94 vs 47.61 ± 41.43 per fellow; P < 0.0001). This reduction was significant across all three training years and for both lower and upper endoscopies (P < 0.0001). However, the reduction in volume was more pronounced for lower endoscopy compared to upper endoscopy [59.03 % (95 % CI: 58.2–59.86) vs 48.75 % (95 % CI: 47.96–49.54); P < 0.0001]. The procedure volume in SP2 returned to near baseline of HP2 (total volume: 42,497 vs 43,275; mean 147.05 ± 96.36 vs 150.78 ± 99.67; P = 0.65).Conclusions Although there was a significant reduction in fellows’ endoscopy volume in the initial stages of the pandemic, adaptive mechanisms have resulted in a return of procedure volume to near baseline without ongoing impact on endoscopy training.